2022
DOI: 10.1126/sciadv.abq5745
|View full text |Cite
|
Sign up to set email alerts
|

An orbitofrontal cortex–anterior insular cortex circuit gates compulsive cocaine use

Abstract: Compulsive drug use, a cardinal symptom of drug addiction, is characterized by persistent substance use despite adverse consequences. However, little is known about the neural circuit mechanisms behind this behavior. Using a footshock-punished cocaine self-administration procedure, we found individual variability of rats in the process of drug addiction, and rats with compulsive cocaine use presented increased neural activity of the anterior insular cortex (aIC) compared with noncompulsive rats. Chemogenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Meanwhile, we also observed that high-frequency DBS of the DRN led to activation in both the OFC and VTA. The OFC plays a fundamental role in motivated behavior, and deficits in its function elicit not only impulsive but also compulsive behaviors, which may underlie the mechanism of compulsive drug seeking and relapse [ 37 , 38 ]. In line with our findings, high-frequency DBS of the OFC has also been shown to reduce the methamphetamine-induced reinstatement of seeking behaviors [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we also observed that high-frequency DBS of the DRN led to activation in both the OFC and VTA. The OFC plays a fundamental role in motivated behavior, and deficits in its function elicit not only impulsive but also compulsive behaviors, which may underlie the mechanism of compulsive drug seeking and relapse [ 37 , 38 ]. In line with our findings, high-frequency DBS of the OFC has also been shown to reduce the methamphetamine-induced reinstatement of seeking behaviors [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building upon the cluster analysis method employed in previous article (Chen, Wang, et al., 2022; Li et al., 2021), we adjusted the behavioral indicators and categorized the animals into stress‐susceptibility and stress‐resilience after SPS. The cluster analysis was conducted utilizing Python.…”
Section: Methodsmentioning
confidence: 99%
“…Building upon the cluster analysis method employed in previous article (Chen, Wang, et al, 2022;Li et al, 2021) ("t-sne" of "sklearn.manifold;" dimension number, 3) was applied to the five normalized variables. The three dimensions were clustered by "Agglomerative Clustering" of "sklearn.cluster."…”
Section: Clustering Analysismentioning
confidence: 99%
“…Imaging studies have reported differential activation of the insula during craving, possibly reflecting interoceptive cues and the activation of corticotropin-releasing factor ( Mar et al, 2011 ). The OFC-anterior insular cortex pathway is also involved in cocaine addiction ( Chen et al, 2022 ) and, interestingly, using a continuous versus intermittent cocaine self-administration paradigm, it has been found that the latter was able to induce greater cocaine-taking behavior during withdrawal ( Luo et al, 2021 ). The same effect, mediated by an intermittent (but not continuous) self-administration paradigm, has been reported for HPF ( Spierling et al, 2020 ).…”
Section: The Mesoaccumbens Dopamine System Involvement In Drug and Fo...mentioning
confidence: 99%